Deep margin elevation for indirect bonded restorations: A case report - Naima Ayari; Ibtissem Grira; Sarra Nasri Soua; Anissa Ben Moussa; Zohra Nouira; Dalenda Hadyaoui; Belhassen Harzallah; Mounir Cherif (Elsevier, 2021)
Introduction: Large posterior defects located beneath the gingival tissues and probably invading the biological width, complicate the use of indirect bonded restorations during rubber dam isolation, impression taking and adhesive procedures.A minimally invasive technique allows to relocate subgingival margin to supragingival level using a resin composite material. This procedure is known as deep margin elevation. Case Description: A 30-year-old female patient, consulted with a restoration loss on molar. The patient was in a good general health. Clinical examination revealed a large sized cavity, associated with cuspal involvement and recurrent carious lesion, extending below the cemento-enamel junction. The treatment plan included a deep margin elevation, followed by an indirect CAD/CAM Lithium disilicate restoration. Discussion: The deep margin elevation procedure decision was based on the presence of deep class II cavity with proximal cervical margin extending below the cemento-enamel junction, the non-invasion of the connective compartment of the biologic width (caries with a margin in the junctional epithelium) and the ability to get a proper isolation using rubber dam and curved matrix. In this case, a two-step etch-and-rinse adhesive system and a combination of restorative and flowable composites were used. The subgingival composite obturation was well tolerated by surrounding tissues. Conclusion/Clinical Significance: Deep margin elevation is a relatively recent technique which benefits seem recognized. The durability of indirect restorations depends on the respect of a correct protocol and the use of appropriate materials.In this case, a two-step etch-and-rinse adhesive system and a combination of a filled hybrid and flowable composites were used.